Multifaceted role of cycling DOF factor 3 (CDF3) in the regulation of flowering time and abiotic stress responses in Arabidopsis. (24th February 2017) - Corrales, Alba‐Rocio; Carrillo, Laura; Lasierra, Pilar; Nebauer, Sergio G.; Dominguez‐Figueroa, Jose; Renau‐Morata, Begoña; Pollmann, Stephan; Granell, Antonio; Molina, Rosa‐Victoria; Vicente‐Carbajosa, Jesús; Medina, Joaquín
Abstract: DNA‐binding with one finger (DOF)‐type transcription factors are involved in many fundamental processes in higher plants, from responses to light and phytohormones to flowering time and seed maturation, but their relation with abiotic stress tolerance is largely unknown. Here, we identify the roles of CDF3, an Arabidopsis DOF gene in abiotic stress responses and developmental processes like flowering time. CDF3 is highly induced by drought, extreme temperatures and abscisic acid treatment. The CDF3 T‐DNA insertion mutant cdf3‐1 is much more sensitive to drought and low temperature stress, whereas CDF 3 overexpression enhances the tolerance of transgenic plants to drought, cold and osmotic stress and promotes late flowering. Transcriptome analysis revealed that CDF3 regulates a set of genes involved in cellular osmoprotection and oxidative stress, including the stress tolerance transcription factors CBFs, DREB2A and ZAT12, which involve both gigantea‐dependent and independent pathways. Consistently, metabolite profiling disclosed that the total amount of some protective metabolites including γ‐aminobutyric acid, proline, glutamine and sucrose were higher in CDF3‐overexpressing plants. Taken together, these results indicate that CDF3 plays a multifaceted role acting on both flowering time and abiotic stress tolerance, in part by controlling the CBF/DREB2A‐CRT/DRE and ZAT10/12 modules. Abstract : The present study provides new notions about the function of DOF Transcription factors and unveils CDF3 as a key factor that display multiple roles related to plant responses to adverse environmental conditions and the developmental programme underlying the transition from vegetative to reproductive phase.